Retrospective Attention in Short-Term Memory Has a Lasting Effect on Long-Term Memory Across Age. (13th April 2018) - Strunk, Jonathan; Morgan, Lauren; Reaves, Sarah; Verhaeghen, Paul; Duarte, Audrey
Abstract: Objectives: Declines in both short- and long-term memory are typical of healthy aging. Recent findings suggest that retrodictive attentional cues ("retro-cues") that indicate the location of to-be-probed items in short-term memory (STM) have a lasting impact on long-term memory (LTM) performance in young adults. Whether older adults can also use retro-cues to facilitate both STM and LTM is unknown. Method: Young and older adults performed a visual STM task in which spatially informative retro-cues or noninformative neutral-cues were presented during STM maintenance of real-world objects. We tested participants' memory at both STM and LTM delays for objects that were previously cued with retrodictive or neutral-cues during STM order to measure the lasting impact of retrospective attention on LTM. Results: Older adults showed reduced STM and LTM capacity compared to young adults. However, they showed similar magnitude retro-cue memory benefits as young adults at both STM and LTM delays. Discussion: To the best of our knowledge, this is the first study to investigate whether retro-cues in STM facilitate the encoding of objects into LTM such that they are more likely to be subsequently retrieved by older adults. Our results support the idea that retrospective attention can be an effective means by which older adults can improve their STM and LTM performance, even in the context of reduced memory capacity.